(untitled) (Circe de clásicos y modernos, 2018)
One typical aspect of the Greek theatre is the tension created in the relationship between not only different spaces but also between places that are visible and those which are not. In this occasion we will focus our attention on the bond, in the Greek tragedy, between the external and the inner spaces in the palace and their point of connection: the σκηνή door. We start from the conviction that this threshold is a key point of analysis, since it connects these spaces which correspond to especially significant appreciations in the Greek imaginary and that, besides, they integrate themselves in a revealing way in the tragic universe. Traquinias presents itself as a privileged play to tackle this issue, since in this play the different spaces and the contact among themselves are fundamental aspects for the development of the plots. In the general framework of the Semiotics of the Theatre, we will approach from the Linguistics of Enuntiation the elements of the δείξιςthat, through the reference to the movement of the actors’ bodies, they organize the discursive space and they make it possible the presence, in the scene, of the hidden dimension of the inner space.